Collaborative Leadership: Principal's Decision Making Strategy in Optimizing Sustainable Digital Based School Culture (DBSC) in the Era of Technological Disruption in Mataram City - Fahmi, Agus; Sumarsono, Raden Bambang (Proceedings Series of Educational Studies, 2024)
This study aims to analyze the decision-making strategies of school principals through collaborative leadership in optimizing a sustainable Digital Based School Culture (DBSC) in the era of technological disruption. This study uses a qualitative approach, SLR type. The procedure is to identify references from various sources using search engines such as Publish or Perish (PoP), science direct, Vos Viewer, Mendeley (referring to the PRISMA pipeline flow), and PRISMA flow diagram creation. The study found that collaborative leadership helps principals create a more technology-responsive school environment, improve digital literacy for all school members, and support the development of sustainable technology infrastructure. However, challenges such as limited technological infrastructure, resistance to change, and lack of digital literacy are still the main obstacles. The results of this study conclude that the optimization of DBSC through collaborative leadership not only improves the quality of education, but also prepares schools to face the demands of future technological developments.